Perceptions of Health and Wellbeing Among Employees in a Work Integration Social Enterprise in Sweden - Gloria Macassa; Cormac McGrath; Michael J. Roy; Frida Stål; Anne Sofie Hiswåls; Mamunur Rashid; Ulf Karlsson; Rooney Olsson; Jose Pedro Silva; Stig Vinberg; Anneli Marttila (Ubiquity Press, 2023)
Background: Work Integration Social Enterprises (WISEs) constitute an important vehicle for providing employment opportunities for disadvantaged groups. Objective: The goal of this qualitative case study is to explore perceptions of health and wellbeing among employees working in a WISE located in the Gävleborg region, in east central Sweden. Methods: Data were gathered using 16 in-depth, semi-structured interviews with the social enterprise employees. Results: Findings were categorized into three main categories: the importance of financial independence and societal benefits; team spirit and a sense of belonging; and improved quality of life and wellbeing. Conclusion: The participants perceived that working in the WISE gave them a feeling of freedom and increased their self-esteem because of the possibility to earn an income. Also, they were satisfied with their job (e.g., with regard to work quality and flexibility) and believed that their work contributed to society. Moreover, through working in a WISE, the participants felt a sense of belonging and togetherness through interaction with co-workers and managers, and an improved quality of life for themselves and their families.